Good practices in Inclusive Education: Review of the role of the teacher during the decade 2010-2020 - et. al., Lorena del Carmen Espina Romero, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Inclusive education is a topic that has gained relevance and interest in the educational field and many researchers have written about its definition, characteristics, barriers and facilitators. However, few are those who place emphasis on good practices and the role that teachers play in materializing them. The purpose of this paper, based on documentary research, is to highlight the work of the inclusive teacher and, likewise, to recognize the value of experiences recognized as good inclusive practices as points of reference to be applied in other less inclusive contexts. A bibliometric analysis of the scientific production registered in the Scopus database on research papers on the role of teachers in inclusive education during the decade between 2010 and 2020 is carried out, the result of which yields 499 published documents that will be subject to quantitative analysis to know their historical and qualitative evolution in order to determine different positions of authors who have written on the topic of study.